Quasilobar minimalist lung volume reduction surgery. (16th April 2021) - Pompeo, Eugenio; Elkhouly, Ahmed; Rogliani, Paola; Dauri, Mario; Peer, Michael; Sergiacomi, Gianluigi; Sorge, Roberto
Abstract:  : OBJECTIVES: Our goal was to assess the results and the costs of the quasilobar minimalist (QLM) thoracoscopic lung volume reduction (LVR) surgical method developed to minimize the trauma from the operation and the anaesthesia and to maximize the effect of the lobar volume reduction. METHODS: Forty patients with severe emphysema underwent QLM-LVR that entailed adoption of sole intercostal block analgesia and lobar plication through a single thoracoscopic incision. Results were compared after propensity matching with 2 control groups undergoing non-awake resectional LVR with double-lumen tracheal intubation or awake non-resectional LVR by plication with thoracic epidural anaesthesia. As a result, we had 3 matched groups of 30 patients each. RESULTS: Baseline forced expiratory volume in 1 s, residual volume, the 6-min walking test and the modified Medical Research Council dyspnoea index were 0.77 ± 0.18, 4.97 ± 0.6, 328 ± 65 and 3.3 ± 0.7, respectively, with no intergroup difference after propensity score matching. The visual pain score was better ( P  < 0.007), the hospital stay was shorter ( P  < 0.04) and overall costs were lower ( P  < 0.04) in the QLM-LVR group than in the control groups. The morbidity rate was lower with QLM-LVR than with non-awake resectional-LVR ( P  = 0.006). Significant improvements ( P  < 0.001) occurred in all study groups during the follow-up period. At 24 months, improvements in residual volume and dyspnoea index were significantly better with QLM-LVR ( P  < 0.04). CONCLUSIONS: QLM-LVR proved safe and showed better perioperative outcomes and lower procedure-related costs than the control groups. Similar clinical benefit occurred at 12 months, but absolute improvements in residual volume and dyspnoea index were better in the QLM-LVR group at 24 months.